Numerical Analysis of Damage Thermo-Mechanical Models (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we present numerical computational methods for solving thefracture problem in brittle and ductile materials with no prior knowledge of the topologyof crack path. Moreover, these methods are capable of modeling the crack initiation.We perform numerical simulations of pieces of brittle material based on globalapproach and taken into account the thermal effect in crack propagation. On the otherhand, we also propose a numerical method for solving the fracture problem in a ductilematerial based on elements deletion method and also using thermo-mechanical behaviorand damage laws. In order to achieve the last purpose, we simulate the orthogonalcutting process.